541. Rapid Migration to Telemedicine in a Boston Community Health Center is Associated with Maintenance of Effective Engagement in HIV Care. (31st December 2020) - Mayer, Kenneth H; Levine, Kenneth; Grasso, Chris; Multani, Ami; Gonzalez, Alex; Biello, Katie
Abstract: Background: The COVID-19 pandemic has disrupted many health care activities. The impact of the pandemic on HIV primary care in a Boston community health center (CHC) that has specialized HIV, sexual and gender minority care is analyzed here. Methods: The CHC has used the Centricity Practice Solution TM electronic medical record (EMR) system since 1997. The current analyses used data abstracted from the EMR, testing for significant differences in HIV care utilization using the Student t-test for means and chi-square tests for proportions. Results: There were 2, 016 HIV+ patients among 25, 606 patients (7.9%) engaged in primary care in 2019. In 2019, HIV+ patients had between 563 and 689 in-person visits per month. On average, monthly visits for HIV care increased (p< 0.0001) in the first two months of 2020 (mean=626, sd=60.1) compared to 2019 (mean=617, sd=40.6), but dropped to 370 and 36 in person visits by HIV+ patients in March and April 2020 respectively (mean=203, sd=236.2; p< 0.0001), when statewide stay-at-home policies were recommended. There were 263 telemedicine visits by HIV+ patients in March and 751 in April, 2020. When telemedicine and in-person visits were combined, mean number of visits per month by HIV+ patients were higher compared to the same two-month period in 2019 (p< .0001). The mean number of plasma HIV RNA viral load (VL) tests performed each month was 279 in 2019 (range 257–312, sd=18.3), versus 219 in March and 274 in April 2020 (mean=246.5, sd=38.9; p< 0.0001). Among those tested, monthly rates of virological suppression ranged from 71–81% in 2019, with 11–20% having VL < 100 copies/ml. Eighty percent had an undetectable VL as their last measurement in 2019; an additional 14% had last VL detectable but < 100 copies/ml. In March and April, 2020, the rates of VL suppression were 77% and 74% and 14% and 18% had VL detectable but < 100 copies/ml, respectively (p=0.209). Conclusion: The COVID-19 pandemic has led to a significant decrease in in-person visits by HIV+ and other patients at a Boston CHC, but with a rapid migration to the use of telemedicine, patient engagement, as expressed by visits and VL suppression does not appear to be adversely affected Disclosures: All Authors : No reported disclosures